Hybrid silylene-Pd catalyst: efficient C-N cross-coupling of sterically bulky amines and chiral amines - Kaulage, Sandeep H.; Parvin, Nasrina; Khopade, Kishor V.; Khan, Shabana (Chemical Communications, 2024)
Herein, we report a catalytic system with N-heterocyclic silylene (NHSi)-phosphine-based hybrid bidentate ligands [PhC(NtBu)2SiN(PR2)(2,6-iPr2-C6H3)] and Pd(dba)2, which serves as an effective catalyst for C-N cross-coupling of a wide range of sterically bulky amines and optically active amines, which is challenging otherwise. Herein, we report a hybrid silylene-based bidentate ligand (SiNP)-Pd(0) catalytic system, which performs the C-N coupling of difficult substrates, e.g., sterically bulky amines and chiral amines.